Relationship of ABO blood group with Hemoglubin level ,glucose level and urinary track infection of pregnant women - A. hasan, Shireen; G. Magtooph, Majida (University of Thi-Qar Journal of Science, 2018)
This study was aimed to determine the relationship between ABO blood group with hemoglobin level ,glucose level and urinary track infection in pregnant women inAL- Naissary city Thi-Qar province ,Iraq .Atotal of 100 pregnant women have beenfound to be screened in this study .Blood samples were collected to examine blood group Hb,and glucose level Also,urine samples were collected to examine urinary track infection .The results showed a significant decrease in hemoglobin level in pregnant women which carried the blood group O when compared with the rest groups(P<0.029) .But there was a significant increase in urinary track infection in the same blood group(P<0.012) . From the another side the blood group type B have significant increase in glucose level(P<0.027) .The finding of the present study was that we the blood group type O was more susceptible to urinary track infection and low level Hb concentration .but the blood group type B was more susceptible to infected with Diabetes.